Fabrication and characterization of Ti–12Mo/xAl2O3 bio-inert composite for dental prosthetic applications - Yehia, Hossam. M.; El-Tantawy, Ahmed; Elkady, Omayma A.; Ghayad, Ibrahim M.; Daoush, Walid M. (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction: Titanium (Ti)-molybdenum(Mo) composites reinforced with ceramic nanoparticles have recently significant interest among researchers as a new type of bio-inert material used for dental prosthetic applications due to its biocompatibility, outstanding physical, mechanical and corrosion properties. The current work investigates the impact of alumina (Al2O3) nanoparticles on the properties of the Ti–12Mo composite, including microstructure, density, hardness, wear resistance, and electrochemical behavior. Methods: Ti–12Mo/xAl2O3 nanocomposites reinforced with different Al2O3 nanoparticles content were prepared. The composition of each sample was adjusted through the mechanical milling of the elemental constituents of the sample for 24 h under an argon atmosphere. The produced nanocomposite powders were then cold-pressed at 600 MPa and sintered at different temperatures (1,350°C, 1,450°C, and 1,500°C) for 90 min. Based on density measurements using the Archimedes method, the most suitable sintering temperature was found to be 1,450°C. The morphology and chemical composition of the milled and sintered composites were analyzed using back-scattering scanning electron microscopy (SEM) and X-ray diffraction (XRD). Results and Discussion: The results showed that the addition of Mo increased the Ti density from 99.11% to 99.46%, while the incorporation of 15wt% Al2O3 in the Ti–12Mo composite decreased the density to 97.28%. Furthermore, the Vickers hardness and wear behavior of the Ti–Mo composite were enhanced with the addition of up to 5 wt% Al2O3. The sample contains 5 wt% Al2O3 exhibited a Vickers hardness of 593.4 HV, compared to 320 HV for pure Ti, and demonstrated the lowest wear rate of 0.0367 mg/min, compared to 0.307 mg/min for pure Ti. Electrochemical investigations revealed that the sintered Ti–12Mo/xAl2O3 nanocomposites displayed higher corrosion resistance against a simulated artificial saliva (AS) solution than pure Ti. The concentrations of Ti, Mo, and Al ions released from the Ti–12Mo/xAl2O3 nanocomposites in the AS solution were within the safe levels. It was found from this study that; the sample of the composition Ti–12Mo/5wt%Al2O3 exhibited appropriate mechanical properties, biocompatibility, corrosion resistance against the AS solution with acceptable ion concentration released in the biological fluids. Therefore, it can be considered as a new bio-inert material for potential applications in dental prosthetics.